Formation mechanism of twin structures in p-type (Bi0.25Sb0.75)2Te3 thermoelectric compound. (15th March 2019) - Lee, Kap Ho; Dharmaiah, Peyala; Hong, Soon-Jik
Abstract: The formation mechanism of twin structures in p-type (Bi0.25 Sb0.75 )2 Te3 compound was examined using high-resolution transmission electron microscopy (HR-TEM) and computer simulations. The results shown that the formation of twins is analogous to the twinning mechanism via synchronized activation of Shockley partial dislocations commonly observed terminating 111 growth and annealing twins in face centered cubic (FCC) metals. The 10 1 ¯ 0 boundary, as an incoherent twin boundary (ITB), is mobile due to its lower shear stress compared to that of the coherent 0001 twin boundary; thickness of the twin region can be reduced or increased according to the direction of the movement. Graphical abstract: Unlabelled Image